Answer:
![x=5\ and\ y=-8](https://tex.z-dn.net/?f=x%3D5%5C%20and%5C%20y%3D-8)
The solution of the system can be given as (5,-8).
Step-by-step explanation:
Given system of equations:
![y=-x-3](https://tex.z-dn.net/?f=y%3D-x-3)
![5x+2y=9](https://tex.z-dn.net/?f=5x%2B2y%3D9)
To solve the given system of equations:
Solution:
We will use substitution to solve the given system.
We will substitute the
values in terms of
from the equation
into the other equation to solve for ![x](https://tex.z-dn.net/?f=x)
Substituting
into
.
We have:
![5x+2(-x-3)=9](https://tex.z-dn.net/?f=5x%2B2%28-x-3%29%3D9)
<em>Using distribution.</em>
![5x-2x-6=9](https://tex.z-dn.net/?f=5x-2x-6%3D9)
<em>Combining like terms.</em>
![3x-6=9](https://tex.z-dn.net/?f=3x-6%3D9)
Adding 6 both sides.
![3x-6+6=9+6](https://tex.z-dn.net/?f=3x-6%2B6%3D9%2B6)
![3x=15](https://tex.z-dn.net/?f=3x%3D15)
Dividing both sides by 3.
![\frac{3x}{3}=\frac{15}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%7D%7B3%7D%3D%5Cfrac%7B15%7D%7B3%7D)
∴ ![x=5](https://tex.z-dn.net/?f=x%3D5)
<em>Plugging in
into
.</em>
We have,
![y=-5-3](https://tex.z-dn.net/?f=y%3D-5-3)
∴ ![y=-8](https://tex.z-dn.net/?f=y%3D-8)
The solution of the system can be given as (5,-8).
Because you are not adding the x's .When you add the coefficients, the variable comes along with it.
You have to upload it from your computer before you press "ADD YOUR ANSWER"
Answer:
0 = (3-2x) x (x x 2 -5)
(3-2x) x ( x x 2 - 5) = 0
(3-2x) x (2x - 5) = 0
3 - 2x = 0
2x - 5 = 0
x = 3/2
x = 5/2
x1 = 3/2 or x2 = 5/2